KARST CITEUREUP UNTUK SUPLEMEN DOKUMEN AMDAL DAN PENAMBANGAN BATUGAMPING - -, Geni Dipatunggoro (Fakultas Teknik Geologi Universitas Padjadjaran, 2006)
Karst can be defined as a peculiar and dry landscape developed as a result of dominantly dissolutional erosion of limestone by rain origin water which enter into the limestone and circulate in the underground drainage then resurgent to the surface as springs. The term karst is derived from the Yugoslavian language “kras” meaning “stone”, and has a root of Italian place Carso. This term is applied to a relative narrow strip of limestone extending along the northeastern coast of the Adriatic Sea.The composition of rocks in the investigated area consists of bioclastic Miocene aged limestone of the Kelapanunggal Formation overlying alternating claystone and sandstone belonging to the Cibulakan Formation of the same age.The Karst developed in investigation areas : 1. Dolines and 2. Kockpit Doline, 3. Swallow Holes, 4.Collapse Cave, 5. Singking Stream and 6. Uvala.